ANALISIS POLA SIRKULASI PENGUNJUNG PADA CELEBRITY FITNESS TRANSTUDIO MALL BANDUNG - Maysitha Fitri Az Zahra; Santi Salayanti (Ide dan Dialog Desain Indonesia (Idealog), 2016)
Celebrity Fitness Transtudio Bandung is a fitness facility contained in Transtudio mall Bandung, located at 3rd floor building. Celebrity Fitness is one of the most popular fitness and much demand in either Indonesia or in the world, because at Celebrity Fitness is available a wide range of programming options classes with professional instructors, as well as a wide variety of selection tools that can be used in accordance with the needs of current visitors is in fitness place. Nowdays, many people in the world, especially urban communities choose an alternative fitness exercise for theirs activity because of their high activity. The higher a person's activity, the less time you have for doing the exercise, so many people are choosing fitness as an alternative to sports. Users fitness today is not only men, many women also were menikuti fitness program in order to maintain health and body ideals. One factor that must be considered in a gym is convenience, visitor comfortness circulation including the appropriate standard. Because one of the things that became Pull at Celebrity Fitness is the user's convenience, the slightest thing related to comfort will be considered in detail. But there are things of interest to writers when using the facilities at Celebrity Fitness Transtudio Bandung, namely the circulation patterns. Linear circulation pattern that is initially quite a good start from the receptionist up to the main workout room, but when on the main exercise room or exercise room TRX towards the path narrowed and sometimes occurs when a buildup of visitors crowded hours. Refinements circulation path is the impact of different forms of space. Shape space indirectly affect the organization of space which affects the circulation space. Celebrity Fitness Transtudio Bandung. Overall comfort and circulation of existing facilities is good enough for standard public space.